KONSEP ILMU PENGETAHUAN SYED HUSSEIN NASHR: SUATU TELAAH RELASI SAINS DAN AGAMA - Hidayatullah, Syarif (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2018)
Syed Hussein Nashr is one of the leading scholars in the field of science and religion relations, especially in Islamic world. A study on Nashr’s thought in this field is an important and necessary effort to understand one of the aspects that contribute particualrly to the development of sciences in the Islamic world, and in the Western world generally. The article aims to understand (1) Syed Hussein Nashr’s concept on science? And (2) the relevance of Nashr’s concept on science to the development of discourses in science and religion? This study focuses on Nashr’sconcept on science and its relevance to the development of the science and religion discourse. This study deploys a framework of philosophy of science, while applying descriptive and analitycal methodological approach. This study finds that: first, Nashr’s concept on science bases it self on the principle of unity, that is a concept of one-ness and inter-relationship of all beings, which allows integration of knowledge and action of human being into harmony. Nashr offers idea of sacred knowledge (scientia sacra) to allow the sacred values embeded in Islamic teaching to spiritualize modern sciences which are developed in the Western world. Secondly, Nashr was the first Muslim scholar who wrote a comprehensive work about history of science in Islam. His influence is attributed to his contribution to the dicsussion of science and to a grand narrative, namely, Islamization of knowledge or Islamic science, that had become a major scholarly debate among Muslim scholars.